Region's reputation and the price of regional products: a hedonic analysis of Portuguese quality cheese - José Cadima Ribeiro; José Freitas Santos (European Regional Science Association (ERSA), 2004)
Resources (tangible and intangible) can be mobilized to increase region's reputation and image giving a competitive advantage to certain products with origin in that region. The returns of a region's resources depend upon the ability of local firms to appropriate the rents earned and whether the consumers value the characteristics of the region that are associated with the product, being disposed to pay a price premium. The estimation of a hedonic price function, which relates the price of Portuguese regional cheeses to its various attributes provided empirical support to test the importance of designation of origin on price. The study showsthat some designations of origin and milk types have a significant impact on price, while retailer format (hypermarket versus online store)and cheese characteristics (cured versus not cured)are nor significant. Specifically, while cheeses from regions of Minho e Trás os Montes and Alentejo are expected to have price premiums, cheeses from regions of Beiras and Ilhas are expected to have discounts. Also, cheeses made with mixed milk and goat's and ewe's milk all have positive effects on price regarding cow's milk (base category).
Keywords: 330